The multifunctionality of agriculture as a tool for agrarian policies analysis: the case of the federal program Sembrando Vida in Chahuites, Oaxaca - Cortez Egremy, Juan Gerardo; Baca del Moral, Julio; Uribe Gómez, Miguel; Gómez Hernández, Teodoro; Valdés Velarde, Eduardo (Acta Universitaria, 2022)
The objective of this article was to expose the use of the multifunctional agriculture approach as a tool for the analysis and evaluation of agrarian policies through a case study carried out in the municipality of Chahuites, Oaxaca, where it was determined the impact that the program Sembrando Vida has on the socioeconomic development of its beneficiaries and on the use and management of natural resources. To this end, a mixed methodology based on three strategies was used: documentary analysis of public policies, frequency analysis, and evidence-based analysis. The results showed a negative impact on the socioeconomic development of the beneficiaries since the economic support is insufficient to fulfill the tasks of the program and to satisfy their basic needs. In the use and management of natural resources, the impact is negative because the program promotes deforestation.